The Impact of Climate Change on Irregular Migration Patterns Across the Libyan Coast: An Analytical Study of Central Route Flows (2022–2024) - Dr. Osama Mohamed Abdel Salam Rashid (Journal of Scientific and Human Dimensions, 2026)
This study aimed to analyze the impact of marine climatic variables on irregular migration patterns across the Libyan coast in the central Mediterranean route during the period 2022–2024. Its methodology was based on descriptive and statistical analysis, by linking migration data issued by the International Organization for Migration and Frontex agency with climatic data provided by NASA's (POWER) database, using correlation coefficients (Pearson and Spearman) to test the relationship between variables. The study also found a clear seasonal pattern, where migration flows increased significantly during the summer due to calm seas, while they decreased in autumn and winter due to adverse climatic conditions (rough seas). The statistical analysis also showed a strong positive relationship between rising temperatures and increased numbers of migrants, and a clear correlation between wind speed and higher rates of deaths and missing persons at sea. The study concluded that climatic factors play an important and pivotal role in determining the timing and volume of migrant flows. Based on this, the study recommends integrating weather indicators and forecasts into early warning systems to support maritime monitoring and rescue operations and mitigate the risks threatening the lives of migrants.
Keywords: Irregular Migration; The Libyan Coast; Climate Change; The Central Route; Human Hazards